(untitled) (Modern information system and technologies, 2018)
The article deals with the factors affecting the demand for information portals to date. Varieties of modern internet portals. The main stages of creating an information portal. Technologies used to create and work with information portals. Analysis of information portal. Keywords: information portal, database, server, search engine, design, data management, portal development, programming